THE FACTORS AFFECTING LABOR DEMAND IN THE FOOD AND TOBACCO INDUSTRY IN NORTH SUMATERA PROVINCE - Sari Wulandari; Sari Fajar Ayu (Universitas Negeri Medan, 2020)
Labor demand in North Sumatra during the period 1991 to 2012 showed a fluctuating condition, where in 2001 is decline. This research aims to analyze the influence of the investment sector, the number of industries, the regional minimum wage and inflation on labor demand sectors of the food industry, beverages and tobacco in North Sumatra Province simultaneously and partially. The data used are secondary data source from Statistics Indonesia of North Sumatra Province namely variable investment industry, the number of industries, the minimum wage, inflation and labor amount of food beverages and tobacco industry in North Sumatra province in the time series from 1991 till 2012 Data analysis wasper formed using OLS (Ordinary Least Square) with multiple linear regression models estimated with the help of the program E-views 7. The results of this study simultaneously changes in industry investment variables, the number of industries, RMW, and inflation significantly influence demand labor sector food industry, beverages and tobacco in North Sumatra Province. While partially concluded that the investment variable number of industry sectors and industries and a significant positive effect, negative effect variables and minimum significant wage, while the inflation variable and no significant negative effect on the demand for labor in the industrial sector of food, beverages and tobacco in North Sumatra Province. The results of this study also showed that the most dominant variable effect on labor demand sectors of the food industry, beverages and tobacco in North Sumatra Province is the minimum wage.